Level of Community Knowledge and Self-Medication Practices Regarding Analgesic Drugs Among Residents of Sukorejo Hamlet, Tempeh Subdistrict, Rw 05 Rt 39, Lumajang - Margareta Cahyaning Arum; Rudy Mardianto; Rakhmadani Gadis Aprilianti (CV. AFDIFAL MAJU BERKAH, 2026)
Health is a state of physical, mental, spiritual, and social well-being that enables everyone to live productively socially and economically. In health maintenance efforts, self-medication, also known as swamedikasi (self-medication), is an alternative taken by the community to increase the affordability of treatment. Improper implementation of self-medication can lead to risks such as medication errors, drug side effects, resistance, and increased treatment costs. For quality self-medication, the community requires correct and clear information. This information must be objective, complete, and not misleading. This study aims to determine the level of knowledge and self-medication of the community about analgesic drugs in the Sukorejo hamlet, Tempeh district, RW 05, RT 39, Lumajang. The research design was descriptive quantitative with a cross-sectional approach. A sample of 55 respondents was selected using purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability, then analyzed using descriptive tests. Based on the results of research on the level of knowledge and self-medication behavior of the community regarding analgesic drugs in Sukorejo Hamlet, Tempeh District, it was found that the level of respondents' knowledge was in the sufficient category, with a total average value of 4.73 (SD = 1.407).